After imprisonment : special issue - Sarat, Austin (Studies in law, politics, and society ;, 2018)
Studies in Law, Politics, andSociety provides a vehicle for the publication of scholarly articles within the broad parameters of interdisciplinary legal scholarship. In this latest editionof this highly successful research series, chapters examine a diverse range oflegal issues and their impact on and intersections with society. This volume features a special section with papers dedicated to life after imprisonment. The chapters examine issues around offender rehabilitation, mass incarceration, and overcriminalization. Other papers included in this important volume address the shift in attitudes to solitary confinement (and the prospect of moving beyond solitary confinement measures) and private prison services. This volume brings together leading scholars and will be vital reading for all those researching in this subject area.